Differential roles between owner and manager in financial practice that contributes to business success: an analysis on Malaysian small business - Azam, S. M. Ferdous; Abdullah, Moha Asri (MCSER Publishing, Rome-Italy, 2015)
The purpose of this research is to assess the moderating effect of business owner and manager in financial practice towards business success in Malaysian small business. To meet the research objectives, this study employed survey method where the unit of analysis is the individual respondent consisting business owners and managers. A sample of 302 data was considered as the final sample size for the current study. Using Structural Equation Modelling (SEM), moderating effects were observed to test the hypotheses. The results indicate that, the owners and managers do have different moderating roles in financial practice to guide the business success in Malaysian small business. Thus, this research conveys an understanding to the entrepreneurs regarding the difference of ownership and managerial role to achieve the business success swiftly. Finally, the current study brings some implications to the policy makers and regulators as well.